Surface Tension of Mixed Solutions of Methyl Acetate and Ethyl Acetate with Cyclohexanone and Acetophenone - Ratsatsi, Lesedi; Ahmad, Jamil (Asian Journal of Chemistry, 2017)
Results of measurement of surface tension on mixed solutions of methyl acetate and ethyl acetate with cyclohexanone and acetophenone are reported. The values are interpreted in terms of intermolecular interactions. Surface tension deviations from linear, additive values, show that the acetophenone interacts with either methyl or ethyl acetate less strongly as compared to cyclohexanone. Similarly ethyl acetate interacts less strongly with either acetophenone or cyclohexanone compared to methyl acetate. The results are interpreted in terms of the relative bulk and the polarizability of the interacting molecules.